Simulation of adaptive power management circuit for hybrid energy harvester and real-time sensing application - M. S. Tamrin; M. R. Ahmad (Institute of Advanced Engineering and Science, 2020)
Many wireless sensor network (WSN) applications, nowadays, require real-time communication, which demands cautious design consideration to resolve inherent conflicts between energy efficiency and the need to meet Quality of Services (QoS), such as end-to-end delay communications. Numerous innovative solutions are proposed such as Real-time Power-Aware Routing (RPAR) protocol, which dynamically adapts transmission power to meet specified communication delays at low energy cost. Hence, to enable real-time communication with RPAR protocol, an adaptive Power Management Circuit (PMC) using hybrid energy harvester to support WSN real-time communication is proposed. In this paper, a high-level architecture of the proposed PMC is discussed, which consists of Thermal Energy Generator (TEG), and Piezoelectric Energy Harvester (PEG) as energy providers, with low-power Maximum Power Point Tracking (MPPT) feature enabled. Preliminary simulations which analyze and characterize TEG and PEG system are conducted separately to determine the optimal design parameters to support the conventional WSN QoS requirement. Next, both systems will be integrated into a single PMC implementation prior to fabrication and lab characterization.